2021
DOI: 10.1212/nxg.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Meta-Analysis for Parkinson Disease Motor Subtypes

Abstract: ObjectiveTo discover genetic determinants of Parkinson disease (PD) motor subtypes, including tremor dominant (TD) and postural instability/gait difficulty (PIGD) forms.MethodsIn 3,212 PD cases of European ancestry, we performed a genome-wide association study (GWAS) examining 2 complementary outcome traits derived from the Unified Parkinson's Disease Rating Scale, including dichotomous motor subtype (TD vs PIGD) or a continuous tremor/PIGD score ratio. Logistic or linear regression models were adjusted for se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…There are several lines of human genetic evidence that indicate a role for ENDOA1 in the development of PD. There are two independent GWAS signals in the vicinity of the SH3GL2 gene that encodes ENDOA1 (Alfradique-Dunham et al, 2021; Chang et al, 2017; Germer et al, 2019; Nalls et al, 2019). Furthermore, there is a risk-conferring missense mutation in the SH3GL2 gene of PD patients (Germer et al, 2019) that encodes a Glycine to Valine transition at position 276 in the flexible region of ENDOA1.…”
Section: Resultsmentioning
confidence: 99%
“…There are several lines of human genetic evidence that indicate a role for ENDOA1 in the development of PD. There are two independent GWAS signals in the vicinity of the SH3GL2 gene that encodes ENDOA1 (Alfradique-Dunham et al, 2021; Chang et al, 2017; Germer et al, 2019; Nalls et al, 2019). Furthermore, there is a risk-conferring missense mutation in the SH3GL2 gene of PD patients (Germer et al, 2019) that encodes a Glycine to Valine transition at position 276 in the flexible region of ENDOA1.…”
Section: Resultsmentioning
confidence: 99%
“…Two large studies from 2021, confirmed that PD patients with APOE E4 allele or GBA variants are at increased risk of faster cognitive deterioration and identified novel polymorphism linked with faster cognitive (RIMS2, TMEM108, and WWOX) and motor (ATP8B2) progression (Liu et al, 2021;Tan et al, 2021). Another GWAS study in 2021, on 3,212 PD cases, did not find any significant association between common variants and PD motor subtypes (TD/PIGD) (Alfradique-Dunham et al, 2021). However, the authors reported multiple suggestive associations, including the polymorphisms of GPNMB (rs199351), SH3GL2 (rs10756907), HIP1R (rs10847864), RIT2 (rs12456492), FBRSL1 (rs11610045), and STK32B (rs2301857) genes (Alfradique-Dunham et al, 2021).…”
Section: Oligo-and Polygenic Genetic Factors Behind Parkinson's Disea...mentioning
confidence: 99%
“…For all NDD but HD, a child term was given, which was also included in the data acquisition step. In total, 153 studies with genomic data were used for the analyses (Maraganore et al, 2005;Fung et al, 2006;Coon et al, 2007;Reiman et al, 2007;Schymick et al, 2007;van Nakamura et al, 2020;Ryu et al, 2020;Alfradique-Dunham et al, 2021;Bone et al, 2021;DeMichele-Sweet et al, 2021;de Rojas et al, 2021;Kang et al, 2021;Loesch et al, 2021;Park et al, 2021;Reddy et al, 2021;Rodrigo and Nyholt, 2021;Sakaue et al, 2021;Schwartzentruber et al, 2021;Shigemizu et al, 2021;Smeland et al, 2021;Tan et al, 2021;Wightman et al, 2021).…”
Section: Data Acquisitionmentioning
confidence: 99%